Out-of-the-box pelvic surgery including iliopsoas resection for recurrent gynecological malignancies: Does that make sense? A single-institution case-series. Issue 4 (April 2017) - Vizzielli, G.; Chiantera, V.; Tinelli, G.; Fagotti, A.; Gallotta, V.; Di Giorgio, A.; Gueli Alletti, S.; Scambia, G.
Abstract: Objective: To report morbidity and oncological outcomes in a consecutive series of lateral isolated recurrent gynecological cancer involving the pelvic side wall (PSW) including the iliopsoas muscle. Material and methods: We retrospectively evaluated a consecutive series between 6/2013 and 12/2015 of lateral isolated recurrent gynecological malignancies treated with a lateral endopelvic resection (LEPR). LEPR was defined as an en-bloc lateral resection of a pelvic tumor with sidewall muscle, and/or bone, and/or major nerve, and/or major vascular structure. Post-surgical complications, quality of life (QoL) and survivals were computed. Results: Seventy-four women with pelvic isolated relapse were admitted for surgery during the study period. Among them, 8 cases (10.8%) showed lateral isolated relapse involving the iliopsoas muscle and were treated with LEPR. R0 resection was achieved in 6/8 patients (75.0%), while the pathologic margins were microscopically and macroscopically positive in 1 patient (12.5%), respectively. There were no perioperative mortalities. Major postoperative complications occurred in 3 patients (37.5%) through peripheral neuropathies, thrombosis of the vascular graft and compartment syndrome of the leg. Median follow-up time was 21 months (range, 12–28). The 2-year overall survival (OS) was 88% improving up to 100% if R0 resection was achieved. In patients with positive pathologic margins (n = 2), the 2-year OS was 50%. All women showed an improved QoL after surgery. Conclusion: LEPR with iliopsoas resection can be safely performed in selected cases with lateral isolated gynecological relapse involving the PSW and was associated with improved QoL and prolonged survival when an R0 resection was achieved.